2007
DOI: 10.1111/j.1574-695x.2006.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of local antibody response againstAlloiococcus otitidisin the middle ear cavity of children with otitis media

Abstract: Alloiococcus otitidis is a recently discovered bacterium frequently associated with otitis media. However, no study is available as to whether A. otitidis has a pathogenic role and induces local immune response in the middle ear as a true pathogen. Whole bacterial sonicate of A. otitidis was separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), and transferred to a nitrocellulose membrane. Then, Western blot analysis was performed with supernatant of the middle ear effusions from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…A. otitidis enhances the expression of an activation antigen, CD69, on human PBMCs, and stimulates the release of T helper type 1 cytokines from PBMCs as well as other middle ear pathogens such as S. pneumoniae [12]. And, children with otitis media produce specific antibodies against A. otitidis in the middle ear cavity [13]. These studies suggest that A. otitidis may have immunostimulating activity.…”
Section: Discussionmentioning
confidence: 96%
“…A. otitidis enhances the expression of an activation antigen, CD69, on human PBMCs, and stimulates the release of T helper type 1 cytokines from PBMCs as well as other middle ear pathogens such as S. pneumoniae [12]. And, children with otitis media produce specific antibodies against A. otitidis in the middle ear cavity [13]. These studies suggest that A. otitidis may have immunostimulating activity.…”
Section: Discussionmentioning
confidence: 96%
“…These results suggest that A. otitidis has the potential to induce these cytokines/ chemokines, contributing to the development of inflammation in the middle ear in a similar manner to S. pneumoniae. Considering the previous finding that A. otitidis becomes immunogenic in the human middle ear [21], this study will help us to understand the association of this organism with otitis media.…”
Section: Discussionmentioning
confidence: 98%
“…In the past, A. otitidis has been considered a commensal of the external ear canal (Frank et al, 2003 ; Tano et al, 2008 ). However, consensus on the role of A. otitidis remains divided, as A. otitidis has been shown to have pathogenic traits including eliciting immune responses in vitro (Himi et al, 2000 ; Tarkkanen et al, 2000 ; Harimaya et al, 2005 , 2007a , b , 2009 ), invading intracellularly (Faden and Dryja, 1989 ) and having been identified as a pathogen in device related (Marchino et al, 2013 ) and chronic infection (Cakar et al, 2013 ). Utilizing culture-independent 16S rRNA sequencing, our department confirmed that A. otitidis and H. influenzae are the two most common bacteria demonstrated in children with OME and that the external ear canal may act as a reservoir for the middle ear (Chan et al, 2017 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%